The impact of cervicogenic headache on patients attending a private physiotherapy practice in Cape Town - I. Diener (AOSIS, 2001)
Headache (HA) disorders constitute a public health problem which impacts on individuals and on society. The functional limitations and participation restrictions caused by chronic HA's may be a more reliable indication of the severity of the disorder than the intensity and HA pattern itself. Evaluation of all these parameters may assist holistic assessment, with impact on the health care of chronic HA sufferers. A quantitative retrospective study of 450 patients' perceptions of the impact of chronic recurrent cervicogenic HA (CRCHA) was done by reviewing clinical notes made at first consultation. Bio-demographic data, Total Pain Pattern and impact of HA's on function, relationships and emotions were recorded using Likert scales. High scores were reported for severe functional disability (60% of the subjects), for considerable emotional handicap (41%) and for negative impact on close relationships (86%). Decreased productivity was reported by 89% of the population studied. Subjects expressed emotions of anxiety (75%), anger (48%) and helplessness (62%). CRCHA has a severe impact on the health-related quality of life of individuals. A combination of these results and existing instruments is currently being used to develop a measuring instrument reflecting a bio-psychosocial approach to assessment. This may improve physiotherapy management of CRCHA patients and may facilitate outcome-based research in this field.